2006
DOI: 10.1212/01.wnl.0000247665.94088.8d
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of Epstein–Barr virus in children with multiple sclerosis

Abstract: We studied seroprevalence and concentrations of Epstein-Barr virus (EBV) antibodies in 147 pediatric patients with multiple sclerosis (MS) and paired controls. The children with MS showed a near-complete seropositivity for EBV antibody against virus capsid antigen (98.6% vs 72.1% in controls, p = 0.001) but did not display serologic evidence for a recent EBV infection. EBV antibody concentrations of pediatric patients with MS were significantly higher vs controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(141 citation statements)
references
References 10 publications
7
133
1
Order By: Relevance
“…Prior EBV infection is thus far the strongest and most consistent environmental factor associated with pediatric and adult‐onset MS 9, 10, 11, 12, 13, 20, 21. We observed that this association with pediatric MS is seen regardless of race and ethnicity, although the association is stronger in whites, as recently reported in adult‐onset MS 14.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Prior EBV infection is thus far the strongest and most consistent environmental factor associated with pediatric and adult‐onset MS 9, 10, 11, 12, 13, 20, 21. We observed that this association with pediatric MS is seen regardless of race and ethnicity, although the association is stronger in whites, as recently reported in adult‐onset MS 14.…”
Section: Discussionsupporting
confidence: 82%
“…Although several other studies investigated the association of prior viral infections and pediatric MS risk,9, 10, 11, 12, 13 very few studies examining the risk of MS in relation to previous viral exposures and the possible interactions with age, race and ethnicity have been conducted 14. Using a large case–control study, we aimed to assess the heterogeneity of association between remote infections with common herpesviruses and the risk of pediatric MS in children with a diverse racial and ethnic background.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of cases positive for this determination (99-100%) was greater than among controls (81-98%), except in the study of Bray et al [23]. In work performed among paediatric subjects, there was also a higher percentage of positive cases, but with differences more accentuated than in adults [17][18][19]. The study performed by Zivadinov et al [43] was the only one in which the proportion of positive results was higher in controls than in cases.…”
Section: Anti-vca Igg Determinationmentioning
confidence: 84%
“…The study performed by Zivadinov et al [43] was the only one in which the proportion of positive results was higher in controls than in cases. The study with the highest OR was published by Pohl et al [19] and that with highest weight was published by Bray et al [23], both of which indicate the existence of an association between the virus and the disease.…”
Section: Anti-vca Igg Determinationmentioning
confidence: 97%
See 1 more Smart Citation